Dobičkonosnost poslovanja gozdarskih družb s koncesijo za izkoriščanje državnih gozdov - Kavčič, Slavka (Gozdarski vestnik, 2008)
The aim of the paper is to analyse overall performance of forestry firms that have a concession to operate and maintain governmental forests and in particular to shed light on the question how the actual amount of the concession affects performance. We compare the method for determination of concession and the budgeted items with the actual revenues and costs to find out whether the concession amount is justified.
Keywords: gozdno gospodarstvo; poslovanje podjetja; državni gozdovi